Destiny and Deliberation: Essays in Philosophical Theology. By Jonathan L. Kvanvig - Arnold, Patrick (The journal of theological studies, 2013)
This work in analytic philosophy of religion engages with contemporary debates on the nature and extent of God’s knowledge and control over temporal events, building on Kvanvig’s many significant contributions to the field. A significant amount of the groundwork is covered in the preface. The goal of the book, Kvanvig explains, is to defend a philosophical Arminianism. This position has two relevant pillars that shape the following chapters. The first is an uncompromising commitment to libertarian free will possessed by humans, and the second is a commitment to the highest possible conception of God. The latter brings Kvanvig close to those in the Augustianian and Reformed tradition, as Kvanvig shares much of their traditional dissatisfaction with open theism, universalism, and Molinism.